Aspectos clínicos, fatores psicológicos e salivares em individuos com Líquen Plano Bucal - Pires, Alessandra Laís Pinho Valente (2016)
Introduction: Lichen Planus is a chronic inflammatory disease of uncertain etiology that may affect skin or mucosa, especially the oral mucosa. Objective: Evaluate the clinical epidemiological profile, and psychological and salivary factors of patients with oral lichen planus. Materials and Methods: The clinical epidemiological profile was assessed by descriptive analysis of 38 dental records of individuals with clinical/pathological diagnosis of oral lichen planus, treated at an Oral Lesions Reference Center in the period between 2005 and 2015 (Article 1). A case control study was conducted to evaluate the levels of anxiety, depression and stress, and both flow and pattern of secretion of salivary cortisol in 42 adults. The experimental group was composed of 21 individuals with a clinical/histopathological diagnosis of oral lichen planus. The control group originated from the same population of cases, consisted of 21 individuals without the disease, randomly admitted and matched to the cases by sex and age. Both groups underwent clinical examination of the oral cavity, structured interview, psychological tests (Beck Anxiety and Depression Inventory and Perceived Stress Scale) and saliva collection at three different times of the day (Article 2). Data was initially analyzed by means of descriptive statistics, by means of absolute and relative frequency and centralization and dispersion steps. Bivariate analysis was performed between the study variables and the presence of oral lichen planus, estimating the odds ratio (OR) as a measure of association, and using confidence intervals at 95%. The Mann-Whitney test was used to compare the groups with regard to scores of anxiety, depression and stress, and the pattern of salivary cortisol secretion. The Friedman test was used to evaluate the pattern of salivary cortisol secretion throughout the day. We used the t-Student test to compare the mean salivary flow between the groups, as well as the area under the curve of the cortisol response to awakening. The correlation between cortisol concentrations with the scores of depression, anxiety, stress and salivary flow was measured through the Spearman correlation coefficient. The adopted significance level was 5%. Results: In Article 1, we observed that 68.42% of the subjects were aged greater than or equal to 40 years; 65.80% were women and 78.90%, had black or brown skin. Most had no systemic disease (68.42%). As for lifestyle, 42.10% were drinkers and 26.30% were smokers. Reticular lichen planus was the most prevalent clinical form (78.13%), mainly affecting the oral mucosa (68.40%). In Article 2, a significant association was found between anxiety scores (p = 0.001), depression (p = 0.005) and perceived stress (p = 0.026), but not when compared to the salivary flow (p = 0.29) or to the pattern of salivary cortisol secretion when waking up (p = 0.98), 30 minutes after waking up (p = 0.95) and at nighttime (p = 0.97). Conclusion: Most cases of lichen planus of the reticular type, usually located in the oral mucosa, occurred in aged over 40, white women. Through psychological tests, it was observed an association between oral lichen planus and anxiety, depression and stress, but not in relation to the analyzed salivary factors.